With the Harmony to Labrador [electronic resource] : notes of a visit to the Moravian mission stations on the north-east coast of Labrador - La Trobe, B. (Benjamin), 1725-1786 (London : Moravian Church and Mission Agency, 1888)
Electronic reproduction. Mode of access: Internet. 44